SENI PEDALANGAN DALAM PENJAJAGAN MASA DEPAN - Suwondo Suwondo (Gelar : Jurnal Seni Budaya, 2007)
Puppetry or the shadow puppet performance has gone into a decrease in its  qualiry and .frequency. This transformation, of course, has positive and negative  impacts. The present puppetry has little chance of being a source of lift guidance for  the Javanese. Unlike puppetry in the past, puppetry as ordinary entertainment does  not take the balance between entertainment and guidance into consideration and is  market-oriented which entertains instantaneouslY so long as it is new and salable.  The importance is that it is livelY and funny and if it is necessary it does not matter  when it creates a pornographic impression. The shadow puppet peiformance has  changed into a commodiry or merchandise.Keywords: Puppetry, commodity, transformation